A Combination of N and S Antigens With IgA and IgG Measurement Strengthens the Accuracy of SARS-CoV-2 Serodiagnostics. (27th April 2021) - Jalkanen, Pinja; Pasternack, Arja; Maljanen, Sari; Melén, Krister; Kolehmainen, Pekka; Huttunen, Moona; Lundberg, Rickard; Tripathi, Lav; Khan, Hira; Ritvos, Mikael A; Naves, Rauno; Haveri, Anu; et al.
Abstract: Background: Primary diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is based on detection of virus RNA in nasopharyngeal swab samples. In addition, analysis of humoral immunity against SARS-CoV-2 has an important role in viral diagnostics and seroprevalence estimates. Methods: We developed and optimized an enzyme immunoassays (EIA) using SARS-CoV-2 nucleoprotein (N), S1 and receptor binding domain (RBD) of the viral spike protein, and N proteins from SARS, Middle East respiratory syndrome (MERS), and 4 low-pathogenic human CoVs. Neutralizing antibody activity was compared with SARS-CoV-2 IgG, IgA, and IgM EIA results. Results: The sensitivity of EIA for detecting immune response in COVID-19 patients (n = 101) was 77% in the acute phase and 100% in the convalescent phase of SARS-CoV-2 infection when N and RBD were used as antigens in IgG and IgA specific EIAs. SARS-CoV-2 infection significantly increased humoral immune responses against the 229E and NL63 N proteins. S1 and RBD-based EIA results had a strong correlation with microneutralization test results. Conclusions: The data indicate a combination of SARS-CoV-2 S1 or RBD and N proteins and analysis of IgG and IgA immunoglobulin classes in sera provide an excellent basis for specific and sensitive serological diagnostics of COVID-19. Abstract : A combination of SARS-CoV-2 N and S antigens and measurement of both IgG and IgA increases the sensitivity of serological diagnostics of COVID-19 and provides a basis for accurate estimation of seroprevalence.